Becoming Parents and Overcoming Obstacles : Understanding the Experience of Miscarriage, Premature Births, Infertility, and Postnatal Depression. - Quagliata, Emanuela (Karnac Books, 2013)
There are many books that deal with pregnancy and maternity, and a large number of magazines and articles on paediatric nursing that examine these subjects from different points of view. This volume is not a manual and is not intended to explain to future parents what to do and what to avoid. The objective is rather to look at the most significant and problematic aspects of this delicate phase of a woman's life and that of a couple. It seeks to offer a key to understand the deep significance and complexity of the path to follow to become parents and to face fears linked to the difficulty of p.